2016
DOI: 10.4067/s0034-98872016000800008
|View full text |Cite
|
Sign up to set email alerts
|

Fisuras labio-palatinas y fortificación de la harina con ácido fólico en Chile: An exploratory study

Abstract: (Rev Med Chile 2016; 144: 1012-1019

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
1

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
(40 reference statements)
0
1
0
1
Order By: Relevance
“…The characteristics of the studies identified since the original review (Johnson & Little, 2008) are presented in Appendix S5, Table S3, which is organized by components or indicators of exposure. Two (Fu, Chen, Huang, & Wu, 2007; Yuan, Lai, Zhou, & Qin, 2007) were published in Chinese, three (Davalos‐Rodriguez et al, 2009; Nazer H & Cifuentes O, 2014; Paulos et al, 2016) in Spanish and 51 in English.…”
Section: Resultsmentioning
confidence: 99%
“…The characteristics of the studies identified since the original review (Johnson & Little, 2008) are presented in Appendix S5, Table S3, which is organized by components or indicators of exposure. Two (Fu, Chen, Huang, & Wu, 2007; Yuan, Lai, Zhou, & Qin, 2007) were published in Chinese, three (Davalos‐Rodriguez et al, 2009; Nazer H & Cifuentes O, 2014; Paulos et al, 2016) in Spanish and 51 in English.…”
Section: Resultsmentioning
confidence: 99%
“…De esta manera, la variable EN (tabla 4) muestra que el 43% de los individuos examinados presenta al menos una de ambas VAM defi ciente. Al estudiar de forma separada el riesgo de RE según VAM T/E e IMC/E se obtiene un OR = 2,4; IC 95% = [1,9] Una forma de entender por qué la VAM T/E presenta un riesgo tan importante para el RE es recordando que esta valoración se remite a evaluar el estado de crecimiento lineal alcanzado en relación a la edad y que su défi cit se relaciona a alteraciones de salud a largo plazo, por ello, es capaz de detectar a aquellos individuos que no se están desarrollando de manera adecuada para su edad lo que es consecuencia de una alteración nutricional en edades tempranas y que acaba traduciéndose en un retraso del desarrollo del niño y de su proceso de erupción dentaria (23,29).…”
Section: Resultsunclassified